HADITH IN COMPARATIVE PERSPECTIVE: TEXTUAL VERIFICATION, AUTHORITY, AND ITS CONTRIBUTION TO GLOBAL SOCIAL ETHICS - Ahmad Iqbal Fajary (Jurnal Ushuluddin, 2026)
This article explores the epistemological position of Hadith within the framework of Comparative Studies of Religions, by analyzing its authority, verification methods, and axiological relevance for peace. In classical Islamic science, Hadith occupies the position of the second authoritative source after the Qur'an, whose function goes beyond mere legal sources (tasyri') to include the foundations of ethics and theological narratives. Using a descriptive-comparative method, this study dissects the unique authentication system of Hadith through isnad (narration chains) and compares it with the methodology of verifying sacred texts in other religious traditions, namely the Historical-Critical method in Biblical studies, the Śruti-Smṛti framework in Hinduism, and the Mahapadesa principle in Buddhism. The analysis shows that despite fundamental methodological differences, all traditions have a common concern for preserving transcendental messages through humane transmission, relying on authoritative communities as guardians. Furthermore, this study highlights the significant axiological potential of the Hadith, by showing how the values of tolerance (ta'aruf), empathy, and proactive peace (sulh) inherent in it provide crucial theological resources for interreligious dialogue and conflict resolution in pluralistic societies. This study concludes that an integrative approach that combines classical epistemology, comparative insight, and peace-oriented hermeneutics, is essential for contemporary Hadith studies to contribute effectively to the global discourse on harmony and coexistence.